Research on process parameter collaborative optimization of non-metal laser cutting based on carbon emission modeling and intuitionistic fuzzy sets. (June 2020) - Bao, Hong; Guo, Sheng; Zhang, Lei; Li, Xinyu
The uncertainty of the optimization process should be taken into account in the energy and material consumption modeling, which is the requisite of the collaborative optimization of low-carbon laser processing parameters. First, it involves establishing the carbon emission boundary based on the carbon source and dividing the non-metallic laser process into scanning and cutting stages, and then analyzing the carbon emission of electric energy, materials, process, and waste recycling of the whole process; all kinds of quantitative models of carbon emission are established. Second, several target intervals are obtained by the intuitionistic fuzzy search algorithm. Combinational experiment with integers in interval is carried out to analyze energy consumption of each combination. Finally, after analyzing the energy consumption influencing factors by comparative test and discussing the cost and time, this article concludes that the carbon emission can be reduced in the process of non-metallic laser processing under the best condition of processing cost and time, and also verifies the proposed quantitative models and the way of analysis by case analysis.